Child labour: forms, causes and implications on education (2015)
This paper focused on child labour, considering forms, causes, and educational implications. Child labour remains a major source of concern in Nigeria despite legislative measures. Forms of child labour include domestic child labour, agricultural child labour, industrial child labour, street hawking/'scavenging, bonded child labour, and commercial sex work. Causes of child labour include poverty, poor schooling opportunity, rapid urbanisation, societal class discrimination and cultural factors among others. Implications of child labour on education include inability to attend classes, high dropout rate due to poor grades, and negative attitude towards school. This paper recommended that education should be made affordable; and that government should improve the quality of education, especially in the area of social security.